2016
DOI: 10.1007/s10792-016-0272-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myopic anisometropia on anterior and posterior ocular segment parameters

Abstract: The purpose of this study is to investigate the differences in anterior and posterior segment parameters of more myopic eyes compared to fellow eyes using spectral domain optical coherence tomography and optical biometer device in patients with myopic anisometropia. This prospective cross-sectional study included 42 myopic anisometropic patients with and without amblyopia, aged between 7 and 40 years old. The refractive error and keratometry values, axial length (AL), central corneal thickness (CCT), peripapil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
3
4
1
Order By: Relevance
“…Our study corroborated with previous studies, 32 34 which have documented a thinner RNFL in myopic subjects. However, some studies have reported a significantly thinner RNFL in more myopic eyes; 35 our study did not find a significant difference.…”
Section: Discussioncontrasting
confidence: 98%
“…Our study corroborated with previous studies, 32 34 which have documented a thinner RNFL in myopic subjects. However, some studies have reported a significantly thinner RNFL in more myopic eyes; 35 our study did not find a significant difference.…”
Section: Discussioncontrasting
confidence: 98%
“…Our findings were in agreement with studies on anisomyopia by Tekin et al [24], Kim et al [25], and Logan et al [26] who found more myopic eyes to be longer and the degree of anisometropia to be correlated with AL difference. Thus, our study supports the hypothesis that axial elongation, rather than K, is the major contributing factor in myopia [2728].…”
Section: Discussionsupporting
confidence: 94%
“…reported a tendency toward a higher amount of spherical myopia in the right eye in Hong Kong myopic anisometropic children and their parents 4 . Similar results have also been reported in other studies 24 . Therefore, to explore if the dominant eye tends to be more myopic, the effect of laterality has to be controlled.…”
Section: Introductionsupporting
confidence: 93%